Developing an assessment model to improve the Sundanese speaking skill of Indonesian middle school students - Kuswari, Usep; Haerudin, Dingding; Nugraha, Haris Santosa (LPMPP Universitas Negeri Yogyakarta, 2022)
The study aims to develop an assessment model of Sundanese language speaking skills for junior high school students in West Java, Indonesia. This test model is expected to provide an effective assessment program, which includes contents, scope, delivery format, and time. A design-based research was adopted to produce a model of class-based Sundanese language and literature learning assessment via several tryouts, interviews, and expert judgment. Findings of this study show that the developed Sundanese Speaking Test Model (SSTM) fits the criteria of a good test in terms of clarity of instruction, clarity of test materials and assessment, use of communicative and standardized language, and use of correct varieties of spoken language. Statistical calculations of field tryout scores show that the assessment model was relevant to field data, indicating that the model is fit and worth using as an assessment instrument of Sundanese speaking skills of junior secondary school students as supported by theoretical concepts and expert judgment. Results of judgment by experts, users, and practitioners also show that the SSTM is reliable for use as an instrument for assessing students’ speaking skills at the middle school level.